Comparative studies on the economic merit of dual-purpose male and standard meat type birds - B. T., Oh; T. K., Mak (1980)
An attempt was made to evaluate the conomic merit of dual-purpose male and standard meat type birds under intensive system of management. In this study 154 dual-purpose males and 153 standard meat type straight-run birds were observed. A micro-computer was under to formulate the least-cost rations. The livability in both flocks was 100%. The differences in feed intake and live weight gain were highly significant. (P<0.01). The dual-purpose birds consumed 46.2% less fed and gained 46.8% less weight than the meat type birds. The feed conversion ratio was not significantly different. Other factors being equal, income over feed and chick costs of meat type bird was $0.64 higher than the dual-purpose bird. The economic margin for meat type and dual-purpose birds were $1.74 and $1.10 per bird respectively.